"Live High-Train High" increases hemoglobin mass in Olympic swimmers - Bonne, T. C.; Lundby, C.; Jørgensen, S.; Johansen, L.; Morgan, M.; Bech, S. R.; Sander, M.; Papoti, M.; Baastrup Nordsborg, N. (European Journal of Applied Physiology, 2014)
Abstract: